The Polemic of Wayang in Da’wah Stage: Digital Contestation for Religious Authority - Umdatul Hasanah; Khairil Anam (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Understanding the polemic of wayang in da'wah, which is being discussed in the digital space, has shown how religious authority is contested. Differences in understanding, group background, culture, interests, and ideology have made the dynamics of the contestation more complex. This article discusses the factors that influence the polemic about the use of wayang in da'wah in the digital space and complements the shortcomings of previous studies. This qualitative research uses the content analysis method on online media data and Twitter for one month. The results of this study indicate that the contestation occurs not only in the gripping and traditional authorities but also in the new authorities who are present amid polemics. The media is part of an authority that has its logic, where media users are free to produce and market ideas in the digital space. This condition becomes a new problem that can undermine traditional authority's power and make the world of da'wah a religious contestation arena.